2016
DOI: 10.1002/chem.201601765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Membrane Pore Formation by Amyloidogenic Peptides in Amyotrophic Lateral Sclerosis

Abstract: Using unbiased atomic-detailed molecular dynamics simulations, the C-terminal fragments of TDP-43 are observed to aggregate and form disordered-toroidal pores in a lipid bilayer. Cytotoxicity of TDP-43 may be inferred from the observation that the membrane pores catalyze lipid flip-flop between bilayer leaflets and conduct water at high rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Here, we report a new methodology that uses unbiased atomic detail folding-partitioning MD simulations to guide rational de novo AMP design. We have previously shown that MD simulations in the multimicrosecond regime are sufficient to capture peptide folding, insertion, and spontaneous oligomerization into structural assemblies in the bilayer at atomic detail. In this approach, fully flexible peptides are allowed to freely assemble and dissociate in the bilayer, thus revealing the structural ensemble present at equilibrium . Like an equivalent laboratory experiment, this approach is completely unbiased.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report a new methodology that uses unbiased atomic detail folding-partitioning MD simulations to guide rational de novo AMP design. We have previously shown that MD simulations in the multimicrosecond regime are sufficient to capture peptide folding, insertion, and spontaneous oligomerization into structural assemblies in the bilayer at atomic detail. In this approach, fully flexible peptides are allowed to freely assemble and dissociate in the bilayer, thus revealing the structural ensemble present at equilibrium . Like an equivalent laboratory experiment, this approach is completely unbiased.…”
Section: Introductionmentioning
confidence: 99%
“…This allows all simulation to be run at 120 °C, increasing pore-formation kinetics. We have previously demonstrated that elevating the temperature does not change conformational equilibria or partitioning free energies of helical membrane-active peptides, provided they are stable against thermal denaturation (see Supplement); however, the vast increase in sampling kinetics at high temperatures allows simulation of peptide folding, bilayer partitioning, and pore assembly without the need for advanced sampling techniques that require additional information or may bias the system 24,47,53,99-103 .…”
Section: Methodsmentioning
confidence: 99%
“…This allows all simulation to be run at 120 °C, increasing pore-formation kinetics. We have previously demonstrated that elevating the temperature does not change conformational equilibria or partitioning free energies of helical A u t h o r a c c e p t e d m a n u s c r i p t membrane-active peptides, provided they are stable against thermal denaturation (Figure S1 and Table S2); however, the vast increase in sampling kinetics at high temperatures allows simulation of peptide folding, bilayer partitioning, and pore assembly without the need for advanced sampling techniques that require additional information or may bias the system (Ulmschneider and Ulmschneider 2008;Ulmschneider et al 2010;Ulmschneider et al 2011;Ulmschneider et al 2014;Chen et al 2014;Chen et al 2016;Chen et al 2019).…”
Section: Macromolecule Release Assaymentioning
confidence: 99%